2016
DOI: 10.53911/jae.2016.2204
|View full text |Cite
|
Sign up to set email alerts
|

Influence of climate change on Helicoverpa armigera (Hubner)in pigeonpea

Abstract: Annual monitoring of the population dynamics of Helicoverpa armigera in unprotected pigeonpea crop during kharif seasons of 2011 to 2014 for 4 years at the farmers field North Gujarat, India. Temperature, rainfall and host-plant species were analyzed with respect to population fluctuation of the insect pest. The observations revealed that, the average number of larval population per plant in the season (from 27th to 3rd standard weeks) was 0.97, 0.32, 0.30 and 0.38 larvae/plant during 2011, 2012, 2013 and 2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
2
1
Order By: Relevance
“…The present finding also got support from the observations of Rathod et al (2017) who reported that the peak larval population of gram pod borer (H. armigera) was recorded in 42 nd SMW (third week of October). The present findings are dissimilar with Jakhar et al (2016) who reported that H. armigera incidence started in 40 th SMW (First week of October) and peak incidence in 43 rd SMW (Fourth week of October). Chaitanya (2012) reported that H. armigera incidence initiated during third week of November and reached peak during second fortnight of December.…”
Section: Population Dynamics Of Helicoverpa Armigera During Kharif 2019contrasting
confidence: 99%
“…The present finding also got support from the observations of Rathod et al (2017) who reported that the peak larval population of gram pod borer (H. armigera) was recorded in 42 nd SMW (third week of October). The present findings are dissimilar with Jakhar et al (2016) who reported that H. armigera incidence started in 40 th SMW (First week of October) and peak incidence in 43 rd SMW (Fourth week of October). Chaitanya (2012) reported that H. armigera incidence initiated during third week of November and reached peak during second fortnight of December.…”
Section: Population Dynamics Of Helicoverpa Armigera During Kharif 2019contrasting
confidence: 99%
“…Factors affected by climate change, such as temperature, rainfall and relative humidity, seem to have mostly positive effects on fecundity and development of migratory pests like locusts 72 , 73 . However, for other lepidopteran pest species, like H. armigera , climate change has negatively affected its survival and reproduction 74 , 75 . Climate change is also reducing the amount of rainfall, which has had an impact on the ecosystem dynamics and vegetation structure of grasses in South Africa reducing grassland areas 76 , but also grass productivity, shifting these grasslands to shrubland and other tree-dominated biomes 77 , 78 .…”
Section: Discussionmentioning
confidence: 99%
“…Beside Coccinellidae, brown lacewings (Neuroptera; Hemerobiidae) and predatory gall midges (Diptera; Cecidomyiidae) are important predator of scale insects (Tandon and Lal, 1978). A wide array of predators and parasitoids has been found to be present and they play important role to control the mango mealy bug populations in mango orchards (Jakhar et al, 2016;Hayat, 2009). Nevertheless, there is no published literature on predator abundance or diversity against mango mealy bug of the species (D. mangiferae) which is one of the important pests of mango.…”
Section: Introductionmentioning
confidence: 99%